Characterisation of enterococci and Escherichia coli isolated from commercial and communal pigs from Mafikeng in the North-West Province, South Africa - Modisane Simon; Moneoang; Bezuidenhout, Cornelius Carlos (African Journal of Pig Farming, 2016)
The aim of this study was to isolate enterococci and Escherichia coli from faeces collected from commercial and communal pigs, and to characterise these isolates using antibiotic susceptibility profiles. Enterococcus selective agar and eosin methylene blue lactose agar were used for enterococci and E. coli isolation, respectively. Gram staining, API 20 Strep and API 20E were used for identification of enterococci and E. coli, respectively. Three-hundred-and-four enterococci and 208 E. coli were identified. The most prevalent enterococci species were Enterococcus faecium (58%) and Enterococcus gallinarum (23%). A large proportion of enterococci (62.5% to 100%) and E. coli (88.5 to 100%) were resistant to erythromycin, oxytetracycline and sulphamethoxazole. No vancomycin-resistant enterococci were found and PCR analysis for vanA, vanB and vanC-1 were all negative. Less than 7% of enterococci were resistant to ampicillin and amoxicillin, whereas 45% of E. coli isolates were resistant to the same antibiotics. Antibiotic susceptibility tests and clustering patterns showed some similarities among these isolates. From the results, a common origin of the isolates or histories of antibiotic use among these farms was proposed. It could also be concluded that vancomycin-resistant enterococci were not present in pigs on these two farms